Homologous cancerous cell membrane modulated multifunctional nanoshuttles: Targeting specificity and improved tumor theranostics. (August 2020) - Cheng, Yanru; Liu, Shuwei; Wang, Lu; Liu, Guojian; Zhao, Pin; Lin, Min; Sui, Kunyan; Zhang, Hao
Abstract: The short lifetime in blood circulation and unspecific uptake of positively charged nanocarriers shed doubt on in vivo applications. Herein, positive charged polyaniline nanoshuttles (Pani NSs) are modified with cancerous cell membranes (CCMs). The Pani NSs/CCMs composites maintain the magnetic resonance imaging (MRI) contrasting and photothermal converting performance in vivo. The CCMs modulation could mainly improve following aspects: 1) Improve the biocompatibility by depressing toxic release of Cu 2+ . 2) Increase the immune invisibility and the half-life (t1/2 ) is prolonged from 4.0 to 13.8 h in blood circulation. 3) The homologous KB tumor targeting efficiency is dramatically enhanced from 3.2 to 11.5 %ID/g. However, elongated t1/2 also reserves the non-homologous tumor uptake rate as 5.6 %ID/g, indicating insufficient targeting specificity of CCMs modulating strategy. This work gives deep understanding for the fundamental necessity of long lifetime in tumor uptake, which is prior to homologous targeting, and it signifies for the functional design and surface modification of nanoagents with enhanced theranostic performance. Graphical abstract: The modification of cancerous cell membranes could efficiently promote tumor uptake rate of nanomaterials. But the long lifetime weakens the targeting specificity of homologous CCMs modulating strategy. Image 1